Interaksi manusia dan gambaran Tuhan dalam kehidupan sehari-hari menurut Emanuel Levinas (kajian filosofis studi kasus pembunuhan mahasiswa di bali ) - Pricilia Elisabet Siahaan; Ribka Cristine Sitorus; Patricia Dwi Irwani Telaumbanua; Yosua Altiel Siburian; Jungjungan Simorangkir (Jurnal Magistra, 2024)
Abstract. Murder cannot be separated from the environment around us. The problem of murder is widespread in today’s life. The aim of this research is to analyze the murder of Aldi Nababan at the Nusa Dua Koi Kos boarding house, Gang Kunci Jalan By Pass Ngurah Rai No.23,Benos, South Kuta (boarding room no. 1st floor)(boarding house),KAB.BANDUNG,SOUTH KUTA,BALI. This research uses studies. The murder that occurred at the Bali boarding house was used for in-depth exploration. Data collection using the internet was carrie out in depth. Based on the analysis, there is a relationship between Emmanuel Levinas’ theory and the murder case of Aldi Nababan. Where Emmanuel Levinas thought said that when we see humans that is where we see the existence of God. Incidents related to murder occurred in Bali because the perpetrator of the murder had no fear of seeing the existence of God in humans.